Frequency of Hereditary Hemochromatosis Gene (HFE) Variants in Sri Lankan Transfusion-Dependent Beta-Thalassemia Patients and Their Association With the Serum Ferritin Level - Padmapani Padeniya; Hemali Goonasekara; Gayan Abeysekera; Rohan Jayasekara; Vajira Dissanayake (Frontiers Media S.A., 2022)
IntroductionCo-inheritance of hereditary hemochromatosis (HFE) gene variants p. C282Y and p.H63D worsen iron overload in transfusion-dependent thalassemia. Data on the HFE gene variants in Sri Lankan patients with thalassemia have not been extensively studied. This study aimed to analyze the p.C282Y and p.H63D variants in transfusion-dependent beta (β) and HbE/β-thalassemia patients and establish an association between these variants and their serum ferritin levels.Materials and MethodsA total of 125 transfusion-dependent β-thalassemia major and HbE/β thalassemia patients were tested for the c.845G>A (p.C282Y) and c.187C>G (p.H63D) HFE gene variants using the multiplex Amplification Refractory Mutation System Polymerase Chain Reaction method. For phenotype-genotype correlation, serum ferritin levels, the erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP) levels were measured. The standard descriptive statistics were used for data analysis.ResultsThe study cohort consisted of transfusion-dependent 123 β-thalassemia and 2 HbE/β-thalassemia patients. The p.C282Y variant was not detected in any patient; allele frequency for the wild type (c.845GG) was 100%. Twenty-three patients were heterozygous for the p.H63D variant allele, and the allele frequencies were c.187CC 91.8%, c.187CG 9.2%, and c.187GG 0%. The mean serum ferritin level was relatively higher (mean level 4,987 ng/ml) in the p.H63D heterozygous (c.187CG) group compared to the wild type (c.187CC) group (mean level 4,571 ng/ml), but the difference was statistically not significant (p = 0.865). Among the total study population, CRP, ESR, and serum glutamine aspartate transaminase (SGPT) were elevated in 9 (7.2%), 65 (52%), and 82 (65.6%) patients, respectively. Among the p.H63D c.187CG group, elevated CRP, ESR, and SGPT were present in 5 (5%), 15 (12%), and 18 (14.4%) patients, respectively. The detected sample number was low to correlate with the confounding effect of inflammatory disorders and liver damage on the serum ferritin levels.ConclusionsThe HFE gene variant p.C282Y is unlikely to cause iron overload in the Asian β-thalassemia patients; the rarity of this variant in the study cohort replicates the findings of other South Asian population studies of this variant. The presence of the p.H63D variant could be a potential risk factor for iron overload in the β-thalassemia patients. A more extensive cohort study is required to validate this finding.